Conceptual Study of Ama and its Manifestation in Various Diseases (International Journal of Ayurveda and Pharma Research, 2022)
Like the theories of Tridosha, Sapta Dhatu, and Trimalas, the concept of Agni and Ama are very unique conceived in Ayurvedic texts. The concept of Ama encompasses an almost whole spectrum of diseases mentioned in Ayurveda. In the Ayurvedic view, nearly all diseases have their origin in Ama dosha. In Ayurveda, the word Ama and Pakva are very important to understand the theories of pathology and treatment according to Ayurveda. The success or failure of the Ayurvedic Physician in treatment depends upon the understanding of two conditions, Sama and Nirama- immature and mature. In Ama dosha langhan or fasting is the general form of treatment. Even medicine is forbidden in acute conditions. As the Jathragni is already weak and struggling to digest Ama, it can’t digest the medicine, another newcomer. The interaction of Doshas, food, and medicine may cause even fatal results.